1996
DOI: 10.1046/j.1365-2508.1996.2610231.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically instilled fluid: the rate of absorption and the effects on patient discomfort and fluid balance

Abstract: The aim of the study was to assess the length of time laparoscopically instilled fluid remains in the peritoneal cavity and to assess its effects on patient discomfort and fluid balance. The setting was a London teaching hospital, and randomized controlled design was used. A total of 24 women undergoing laparoscopic surgery were randomized, one group (n = 12) received 1 l of normal saline instilled into the pouch of Douglas at the end of surgery, and the other (n = 12) acted as controls. A vacuum drain was lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…This finding can be predicted, as crystalloids at this volume are absorbed from the peritoneal cavity at the rate of 30-50 mL/hour. At this rate there is likely to be little crystalloid solution remaining in the pelvis after 24 hours (27)(28)(29). A recent study examining absorption of 2 L of crystalloid solutions suggested that approximately 500 mL remained 24 hours later (35).…”
Section: Figure 11mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can be predicted, as crystalloids at this volume are absorbed from the peritoneal cavity at the rate of 30-50 mL/hour. At this rate there is likely to be little crystalloid solution remaining in the pelvis after 24 hours (27)(28)(29). A recent study examining absorption of 2 L of crystalloid solutions suggested that approximately 500 mL remained 24 hours later (35).…”
Section: Figure 11mentioning
confidence: 99%
“…Crystalloid solutions, such as lactated Ringer's solution (LRS), phosphate-buffered saline (PBS), and normal saline, are commonly used but are not approved for use as adhesion reduction agents. Small volumes of 200-500 mL are usually instilled (27); however, as this type of solution is absorbed at an approximate rate of 30-50 mL/hour (27)(28)(29), 200 mL LRS would be absorbed in approximately 6 hours (27). Transvaginal ultrasound assessment of LRS has shown that within 24 hours, a 250 mL surgical instillate volume would have diminished to an undetectable level (30).…”
mentioning
confidence: 99%
“…However, these crystalloid solutions are absorbed rapidly and do not reduce adhesions [53]. They are absorbed from the peritoneal cavity at the rate of 30-50 ml per hour, so that, by 24 hours after surgery, little, if any, solution is left in the pelvis [54][55][56]. Studies have also shown that some irrigants, including lactated Ringer's solution, can have deleterious effects on the delicate mesothelial lining of the peritoneum [57,58].…”
Section: Broad-coverage Fluid Agentsmentioning
confidence: 99%
“…The rapid absorption of Ringer's lactate from the peritoneal cavity within 24 hours, and thus its absence during the critical period when adhesion formation occurs, in the first 4-7 days postoperatively, may be the reason (24,41). In contrast, residues of PVA gel, found in several animals 21 days after application, suggest protracted absorption.…”
Section: Lang Viscous Adhesion Barrier Fertil Steril 2007mentioning
confidence: 99%